Adherence to the American Cancer Society Guidelines on nutrition and physical activity for cancer prevention and obesity‐related cancer risk and mortality in Black and Latina Women's Health Initiative participants. Issue 20 (23rd August 2022) - Pichardo, Margaret S.; Esserman, Denise; Ferrucci, Leah M.; Molina, Yamile; Chlebowski, Rowan T.; Pan, Kathy; Garcia, David O.; Lane, Dorothy S.; Shadyab, Aladdin H.; Lopez‐Pentecost, Melissa; Luo, Juhua; Kato, Ikuko; et al.
Abstract : Background: Although adherence to the American Cancer Society (ACS) Guidelines on Nutrition and Physical Activity for Cancer Prevention associates with lower risk of obesity‐related cancer (ORC) incidence and mortality, evidence in Black and Latina women is limited. This association was examined in Black and Latina participants in the Women's Health Initiative (WHI). Methods: Semi‐Markov multistate model examined the association between ACS guideline adherence and ORC incidence and mortality in the presence of competing events, combined and separately, for 9301 Black and 4221 Latina postmenopausal women. Additionally, ACS guideline adherence was examined in a subset of less common ORCs and potential effect modification by neighborhood socioeconomic status and smoking. Results: Over a median of 11.1, 12.5, and 3.7 years of follow‐up for incidence, nonconditional mortality, and conditional mortality, respectively, 1191 ORCs (Black/Latina women: 841/269), 1970 all‐cause deaths (Black/Latina women: 1576/394), and 341 ORC‐related deaths (Black/Latina women: 259/82) were observed. Higher ACS guideline adherence was associated with lower ORC incidence for both Black (cause‐specific hazard ratio [CSHR]highvs.low : 0.72; 95% CI, 0.55–0.94) and Latina (CSHRhighvs.low : 0.58, 95% CI, 0.36–0.93) women; but not conditional all‐cause mortality (Black hazard ratio [HR]highvs.low : 0.86; 95% CI, 0.53–1.39; Latina HRhighvs.low : 0.81; 95% CI, 0.32–2.06). Higher adherence was associated with lower incidence of less common ORC ( P trend = .025), but conditional mortality events were limited. Adherence and ORC‐specific deaths were not associated and there was no evidence of effect modification. Conclusions: Adherence to the ACS guidelines was associated with lower risk of ORCs and less common ORCs but was not for conditional ORC‐related mortality. Lay summary: Evidence on the association between the American Cancer Society Guidelines on Nutrition and Physical Activity for Cancer Prevention and cancer remains scarce for women of color. Adherence to the guidelines and risk of developing one of 13 obesity‐related cancers among Black and Latina women in the Women's Health Initiative was examined. Women who followed the lifestyle guidelines had 28% to 42% lower risk of obesity‐related cancer. These findings support public health interventions to reduce growing racial/ethnic disparities in obesity‐related cancers. Abstract : Black and Latina women who followed the American Cancer Society guidelines on nutrition and physical activity for cancer prevention experienced lower incidence of obesity related cancers. These findings support public health education and interventions to reduce growing racial/ethnic disparities in incidence of obesity‐related cancers.